Uji aktivitas ekstrak etanol daun kemangi (Ocimum bacilicum L) pada mencit putih jantan yang di induksi amnesia - Andriani, Yuni; Almahdy, Almahdy; Fauziah, Fauziah (Tropharm (Trobosan Pharmacy); Vol 1 No 1 (2015): Tropharm (Trobosan Pharmacy), 2021)
Basil (Ocimum bacilicum L) was known having effect in central nervous system such  anti-depressant, sedative and anti-seizure. Peoples often use it as fever, epilepsy, headache, launched breast milk  and facilitating menstruation. Basil leave contain many essential oils as anti-depressant and flavonoid as anti-oksidan. The aim of the study is to look at the activity of the ethanol extract of  basil leave on the central nervous system of the male white mice induced amnesia seen in cognitive function. Experimental animals were divided into five groups, control group and the groups was given the extract 100, 300, 500 mg/kgBB p.o for 7 day and piracetam as a comparator drug 500 mg/kgBB i.p, on day 8 mice in the induction of diazepam, testing against memory  using  Y maze, the parameter is the travel time seen rats to find food / pellets as reword.  The results of research showed the ethanol extract of leaves basil with every dose and drug pirasetam in mice induced amnesia may improve memory significantly (P<0,05).